2021
DOI: 10.3390/cancers13184559
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Incorporating Host Factors for Predicting Survival in Head and Neck Squamous Cell Carcinoma Patients

Abstract: Prognostication for cancer patients is integral for patient counseling and treatment planning, yet providing accurate prediction can be challenging using existing patient-specific clinical indicators and host factors. In this work, we evaluated common machine learning models in predicting head and neck squamous cell carcinoma (HNSCC) patients’ overall survival based on demographic, clinical features and host factors. We found random survival forest had best performance among the models evaluated, which achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…[22][23][24][25]28,29 Such discrepancies may be due to a nonlinear association between BMI and survival, with the highest survival seen in the overweight BMI range. 33,34 To our knowledge, this is the first report for head and neck cancer to show that overweight BMI and obese BMI are associated with complete metabolic response on follow-up PET-CT. Our finding is consistent with another study suggesting a higher likelihood of pathologic complete response in…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…[22][23][24][25]28,29 Such discrepancies may be due to a nonlinear association between BMI and survival, with the highest survival seen in the overweight BMI range. 33,34 To our knowledge, this is the first report for head and neck cancer to show that overweight BMI and obese BMI are associated with complete metabolic response on follow-up PET-CT. Our finding is consistent with another study suggesting a higher likelihood of pathologic complete response in…”
Section: Discussionmentioning
confidence: 79%
“…32,51 Although a few other studies have suggested that a higher BMI is associated with improved survival, 41 they also included patients with an underweight BMI as a reference group, which was previously shown to be associated with worse survival outcomes. 33,34 Although a lack of association between BMI, HPV, and survival in our study may be due to smaller subgroup sample sizes, interaction among these variables warrants further investigation. For example, despite adipose tissue-promoting pathways, including PI3K-PTEN-Akt-mTOR and Ras-Raf-MAPK associated with HPV-associated head and neck cancers, 52 patients with a high BMI were more…”
Section: Jama Network Open | Oncologymentioning
confidence: 74%
“… 40 , 41 Another method to improve patient selection for survival outcomes is to incorporate machine learning to account for complex interactions with other host factors. 42 Although a phase 3 trial failed to show improved locoregional control with radiation dose escalation, 43 a recent study also investigated the feasibility of adaptive dose escalation among those with poor survival outcomes. 44 Further studies would be warranted to improve risk stratification and tailor effective treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent work, Yu et al [1] evaluated almost 600 primary HNSCC patients treated with definitive or post-operative RT. The authors showed through a machinelearning model that the main predictors of patients' overall survival were performance status, body-mass index (BMI) and the host factors reflecting the patients' nutrition and inflammation status.…”
Section: Introductionmentioning
confidence: 99%